A modelling study of the Bjerknes compensation in the meridional heat transport in a freshening ocean - Yang, Haijun; Wang, Yuxing; Liu, Zhengyu (Tellus A: Dynamic Meteorology and Oceanography, 2013)
The compensation between the meridional heat transports in the atmosphere and ocean is studied through a coupled model's water-hosing experiments. It is found that the atmospheric heat transport (AHT) change compensates the oceanic heat transport (OHT) change very well in the extratropics, while the former overcompensates the latter in the tropics. Similar to previous studies, the fresh water input in the high latitude Atlantic weakens the Atlantic meridional overturning circulation and thus the northward Atlantic OHT significantly, leading to a warming (cooling) in sea surface temperature in the Southern (Northern) Hemisphere and in turn a southward shift of atmospheric convection. This results in an enhanced Hadley Cell (HC) and stronger northward AHT, compensating the reduced Atlantic OHT. Meanwhile, the wind-driven Subtropical Cell in the Indo-Pacific oceans is enhanced in response to the HC change, increasing the northward OHT in the Indo-Pacific, which partly offsets the reduced OHT in the Atlantic. The response in the Indo-Pacific is responsible for the overcompensation of the AHT to the global OHT. The Held's mechanism works very well in the tropical Indo-Pacific in our experiments. This is substantially different from previous studies. http://gateway.webofknowledge.com/gateway/Gateway.cgi?GWVersion=2&SrcApp=PARTNER_APP&SrcAuth=LinksAMR&KeyUT=WOS:000319401300001&DestLinkType=FullRecord&DestApp=ALL_WOS&UsrCustomerID=8e1609b174ce4e31116a60747a720701 Meteorology & Atmospheric Sciences Oceanography SCI(E) 10 ARTICLE null 65